Zinc Oxide Nanoparticles Mitigate Toxic Effects of Cadmium Heavy Metal in Chilli (Capsicum annuum L.) - Syed Mazhar Irfan; Khizar Hayat Bhatti (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2023)
Heavy metals contaminated soils and water sources are one of the major global causes of inhibition of plant growth and productivity. Different strategies are being employed to overcome the challenging issue to increase plant yield requirements to fulfil the needs of future generations. The objective of the present study was to observe the effects of spray (foliar) of green synthesized ZnO nanoparticles (100 ppm), alone and its interaction in conjugation with Cd (Cd+ZnO-NPs) 100 ppm of both on the growth and biochemical activities of the target plant, i.e., two chilli varieties. After two weeks of transplant, treatments viz., Control (T1), ZnO nanoparticles 100 ppm (T2), Cd 100 ppm (T3), and ZnO nanoparticles 100 ppm + Cd 100 ppm (T4) were given for six weeks and different parameters of growth and biochemical analysis were made. Results have shown that 100 ppm foliar spray of ZnO-NPs has significantly increasing effects on root and shoot growth of chilli plants in alone (ZnO nanoparticles) and Combined (ZnO nanoparticles +Cd heavy metal) treatments mitigating toxic effects of Cd stress. A similar increase in values of total carbohydrates, soluble proteins, free amino acids, and photosynthetic pigments were observed mostly in a combination of Cd+ZnO-NPs treatment showing remediation properties of ZnO nanoparticles against Cd stress in chilli plant. In conclusion, it may be suggested that 100 ppm ZnO-NPs foliar spray can have an increasing effect on the growth parameters of the plants under stressful conditions of Cd heavy metal.